Trochanterické zlomeniny femuru - Douša, Pavel; Čech, Oldřich; Weissinger, Manfred; Džupa, Valér (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2013)
At the present time proximal femoral fractures account for 30% of all fractures referred to hospitals for treatment. Our population is ageing, the proportion of patients with post-menopausal or senile osteoporosis is increasing and therefore the number of proximal femoral fractures requiring urgent treatment is growing too. In the age category of 50 years and older, the incidence of these fractures has increased exponentially. Our department serves as a trauma centre for half of Prague and part of the Central Bohemia Region with a population of 1 150 000. Prague in particular has a high number of elderly citizens. Our experience is based on extensive clinical data obtained from the Register of Proximal Femoral Fractures established in 1997. During 14 years, 4280 patients, 3112 women and 1168 men, were admitted to our department for treatment of proximal femoral fractures. All patients were followed up until healing or development of complications. In the group understudy, 82% were patients older than 70 years; 72% of those requiring surgery were in their seventies and eighties. Men were significantly younger than women (p<0.001) and represented 30% of the group. The fractures were 2.3-times more frequent in women than in men. In the category under 60 years, men significantly outnumbered women (p<0.001). The patients with pertrochanteric fractures were, on the average, eight years older than the patients with intertrochanteric fractures, which is a significant difference (p<0.001). The mortality rate within a year of injury was about 30%. Trochanteric fractures accounted for 54.7% and femoral neck fractures for 45.3% of all fractures. The inter-annual increase was 5.9%, with more trochanteric than femoral neck fractures. There was a non-significant decrease in intertrochanteric (AO 31-A3) fractures. On the other hand, the number of pertrochanteric (AO 31-A1+2) fractures increased significantly (p<0.001). A total of 1 394 fractures were treated with a proximal femoral nail; a short nail was used in 1260 and a long nail in 134 of them. A dynamic hip screw (DHS) was employed to treat 947 fractures. Distinguishing between pertrochanteric (21-A1, 31-A2) and intertrochanteric (31 -A3) fractures is considered an important approach because of their different behaviour at reduction. Pertrochanteric fractures occurred more frequently (81.5%); the patients' age was higher (80 years on the average) and women outnumbered men at a ratio of 3:1. Intertrochanteric fractures were found in significantly younger patients (average, 72 years), with a women-to-men ratio of 1.3:1. Stable pertrochanteric fractures (31-A1) were preferably indicated for DHS surgery. Unstable pertrochanteric (31-A2) and intertrochanteric (31-A3) fractures were treated with a nail. The patients underwent surgery on the day of injury or the next day. In the case of contraindications to an urgent intervention, surgery was performed after the patient's medical condition had stabilised. The number of complications was largely related to technical errors, such as insufficient reduction or an incorrectly inserted implant. Intertrochanteric fractures were associated with a higher occurrence of complications. No implant can compensate for errors due to surgery. Serious complications can be reduced by the correct assessment of fracture type, the use of an appropriate operative technique and early treatment of potential complications. The necessity of restoring continuity in the medial cortex of the femoral neck (Adams' arch) is the requirement that should be observed. Pseudoarthrosis or varus malalignment in a healed hip should be managed by valgus osteotomy. When the femoral head or the acetabulum is damaged, total hip arthroplasty is indicated. A prerequisite for successful surgical outcome is urgently and correctly performed osteosynthesis allowing for early rehabilitation and mobilisation of the patient
Keywords: Female; kyčelní protézy; fraktury kyčle; intramedulární fixace fraktury; ženské pohlaví; kostní šrouby; lidé; pooperační komplikace; Hip Fractures; Fracture Fixation, Intramedullary; Postoperative Complications; Male; Aged; dlahy; senioři; mužské pohlaví; Splints; Hip Prosthesis; Bone Screws; Humans